THE IMPLEMENTATION OF TEACHING ENGLISH THROUGH CHILD GAMES BASED ON LOCAL CULTURE AT SD MUSLIM CENDEKIA - Maylian Giofany (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This present study aims to determine the implementation of teaching English through child games-based on local culture at SD Muslim Cendekia. This study also sought to reveal whether there are advantages in the use of such games. The researcher used a qualitative descriptive research design with a sample of 1 English teacher and 6 students. The instruments used in this study were interviews and documentation. Analysis of data used the data collection, data reduction, display the data, and conclusion. The result showed that local culture based-child games were one of the strategies to teach young learners based on teacher and students on the use of games. The games-based on local culture used are snakes and ladder and go to the zoo. This game is very effectively used in learning speaking and writing skills. In the snakes and ladder game, the focus is more on learning speaking skills, because students are required to make a reflex question or sentence. In the go to zoo game, it focuses more on learning speaking and writing skills, because students are required to make simple sentences and present the results in front of the class. It would be much effective than if the teacher gave only theories. The students would also easily remember what they learned in their lessons by using games. Moreover, the results also demonstrated that the use of games was a way to make the lessons more effective, interesting, and enjoyable for students. Keywords: Young learners, child games, games-based on local culture